The girl who invented romance - Cooney, Caroline B. (New York : Bantam Books, 1988)
While waiting for her first big romance and observing the sometimes rocky love affairs of her parents and brother, sixteen-year-old Kelly develops a board game called Romance.
Booklist.
6.5
6.5
7-10.
Young Adult
Keywords: Love -- Fiction; Love stories